Global Economic Landscape: From 5 ‘G’ To Polycrisis, and the Outlook Scenarios - Azis, Iwan J (Muslim Business and Economics Review, 2023)
Learning from ‘Great Moderation’ to the ongoing ‘Geoeconomic Fragmentation,’ past episodes of capital flows can explain the evolution of global economy and the associated vulnerabilities. The events in all episodes are related to one another, and the corresponding vulnerabilities are interrelated. Together with the expected and unexpected contemporary shocks (pandemic, wars, geopolitical tensions) the built-up vulnerabilities contribute indirectly to the current sorry-state of global economy. As uncertainties abound, and the world is in polycrisis, it is difficult to forecast what is going to happen. Any estimate, including those made by the international organizations are subject to change. The outlook scenarios mapped out in this paper is intended to help us just to frame thinking about the potential paths ahead.